2008
DOI: 10.1590/s0101-81752008000400005
|View full text |Cite
|
Sign up to set email alerts
|

The megalopa and early juvenile development of Hepatus pudibundus (Crustacea: Brachyura: Aethroidea) reared from neuston samples

Abstract: ABSTRACT. Hepatus pudibundus (Herbst, 1785) is a crab commonly found in shallow waters of the Western Atlantic. Its larval and early post-larval morphology have already been described from laboratory hatched material. Around 200 megalopae of H. pudibundus were collected in neuston samples from the Ubatuba region, Brazil, during the summer of 2005-2006 and were successfully reared under laboratory conditions. The size of the megalopae obtained in the neuston was similar to those specimens previously described i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Although H. pudibundus is an important species in the food webs of unconsolidated sediments along the infralittoral (Mantelatto & Petracco 1997), most previous studies focused on biological aspects, including larval and juvenile development in the laboratory and from field samplings (Rieger & Hebling 1993, Hebling & Rieger 2003, Negreiros-Fransozo et al 2008, population structure (Mantelatto et al 1995b, Fracasso & Branco 2005, Klôh & Di Beneditto 2010, Lima et al 2014a, morphometry , 1994, feeding strategies (Mantelatto & Petracco 1997), reproductive biology (Reigada & Negreiros-Fransozo 1999, Lima et al 2014b, and growth and mortality (Keunecke et al 2007). A few studies focused on H. pudibundus distribution (Mantelatto et al 1995a, Lima et al 2014a, but none of them included areas of 20 m in depth or deeper.…”
Section: Introductionmentioning
confidence: 99%
“…Although H. pudibundus is an important species in the food webs of unconsolidated sediments along the infralittoral (Mantelatto & Petracco 1997), most previous studies focused on biological aspects, including larval and juvenile development in the laboratory and from field samplings (Rieger & Hebling 1993, Hebling & Rieger 2003, Negreiros-Fransozo et al 2008, population structure (Mantelatto et al 1995b, Fracasso & Branco 2005, Klôh & Di Beneditto 2010, Lima et al 2014a, morphometry , 1994, feeding strategies (Mantelatto & Petracco 1997), reproductive biology (Reigada & Negreiros-Fransozo 1999, Lima et al 2014b, and growth and mortality (Keunecke et al 2007). A few studies focused on H. pudibundus distribution (Mantelatto et al 1995a, Lima et al 2014a, but none of them included areas of 20 m in depth or deeper.…”
Section: Introductionmentioning
confidence: 99%
“…The differences during larval development relate to the changes in environmental conditions, such as the mixture of water masses, food deficiency or changes in temperature Morphological variations on megalopa of C. antillensis Nauplius, 26: e2018031 and salinity. This flexibility is an evolutionary and ecological strategy which enhances survival and allows the distribution of the larvae to be extended (Welch and Epifanio, 1995;Hartnoll, 2001;Thatje and Bacardit, 2000;Negreiros-Fransozo et al, 2008). In this respect, Tirmizi and Siddiqui (1980), McLaughlin and Gore (1988) and Siddiqui et al (1991) found differences in the setation and spination of Pagurus kulkarnii Sankolli, 1962, Pagurus hirsutiusculus (Dana, 1851) and C. antilliensis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to this species have focused on aspects of their distribution and population structure (Mantelatto et al ., 1995 a , 1995 b ; Martínez et al ., 2009; Klôh & Di Beneditto, 2010; Sardá et al ., 2013; Lima et al ., 2014 a ), the relationship of weight to carapace width, relative growth and sexual dimorphism (Mantelatto & Fransozo, 1992, 1994; Marochi et al ., 2016), sexual maturity and reproductive cycle (Reigada & Negreiros-Fransozo, 1999, 2000), individual growth and mortality (Keunecke et al ., 2007), reproductive biology (Lima et al ., 2014 b ) and juvenile development (Hebling & Rieger, 2003; Negreiros-Fransozo et al ., 2008). Considering the ecological importance and the abundance of H. pudibundus in the by-catch of penaeid shrimp, the present study analysed the population dynamics of this species in the region of Cananéia, on the southern coast of São Paulo state in Brazil during two years of samplings.…”
Section: Introductionmentioning
confidence: 99%